Propaganda wojenna w kazaniach patriarchy moskiewskiego i całej Rusi Cyryla I. Próba analizy pragmalingwistycznej - Kondzioła-Pich, Katarzyna (Przegląd Wschodnioeuropejski, 2025)
The aim of this article is to examine the head of the Russian Orthodox Church, Ciril I, official statements about the Russian-Ukrainian war, concentrating on the issue of how both participants of the conflict are presented. The analysis was based on the sermons of Ciril I, that the patriarch has given from Feb. 2022 to Feb. 2024. The sermons were studied in concordance with the principles of pragmalinguistics. The sermons of the Russian patriarch were identified as evidently partial, because the goal of his statements is to effect on the attitude to war of his listeners. It must be admitted that the demeanour of Ciril’s hearers should totally correspond with the Russian authorities’ perspective. The analysis has proved that the character of the vocabulary and the types of the strategies of communication used by Ciril I in his sermons let us treat them as one of the crucial elements of Russian propaganda for war.